The effect of physical and mental stress on the heart rate, cortisol and lactate concentrations in rock climbers - Magiera, A.; Roczniok, R.; Sadowska-Krepa, E.; Kempa, K.; Placek, O.; Mostowik, A. (Journal of Human Kinetics, 2018)
Rock climbing is a physical activity that not only causes an increase in muscle tension, heart rate and blood pressure, but also results in the elevation of stress hormones including cortisol. It has not been established which of the above mentioned variables serve as the most accurate indicator of rock climbing-induced physical and mental stress. The aim of this study was to evaluate the effect of physical activity, short-term fatigue and mental demand on heart rate (HR), salivary cortisol (C) and blood plasma lactate (LA) concentrations in rock climbers under laboratory conditions. Twelve male and female rock climbers of comparable climbing performance (5a - 6b OS) were recruited. The participants completed two routes of different climbing difficulty (effect of physical demand), repeated a difficult route with a short 5-min recovery period three times (effect of fatigue), and repeated a difficult lead climb (effect of mental demand). Heart rate as well as C and LA concentrations were determined. The results indicated that more difficult climbing routes elicited increases in HR (especially relative values) and LA concentrations, whereas fatigue accumulation had an effect on climbing HR and relative C concentration values. Lead climbing only caused an increase in climbing HR. Based on the results it was concluded that HR was a good indicator of physical and mental stress intensity. Performing the same difficult route three times with a short recovery period in-between turned out to be the most demanding task and resulted in the highest increase of the cortisol concentration. Dynamics of changes in lactate concentrations depend on muscle loading (local muscular effort), lactate clearance and technical/tactical skills of the climber.